Outcome of poor response paediatric AML using early SCT. (20th January 2013) - Wareham, Neval E.; Heilmann, Carsten; Abrahamsson, Jonas; Forestier, Erik; Gustafsson, Britt; Ha, Shau‐Yin; Heldrup, Jesper; Jahnukainen, Kirsi; Jónsson, Ólafur G.; Lausen, Birgitte; Palle, Josefine; Zeller, Bernward; et al.
Abstract Background Children with poor response acute myeloid leukaemia (AML) generally have a very poor outcome. Allogeneic stem cell transplantation (SCT) is often recommended for these children but the benefit is unclear. The aim of this study was to investigate survival for poor response AML patients treated with SCT. Material and Methods Treatment was given according to the NOPHO‐AML 2004 protocol. All patients received AIET (Cytarabine, Idarubicin, Etoposide, Thioguanine) and AM (Cytarabine, Mitoxantrone) as induction. We included poor response defined as > 15% blasts on day 15 after AIET (n = 17) or > 5% blasts after AM (n = 14, refractory disease). Poor response patients received intensively timed induction and proceeded to SCT when a donor was available. Results Thirty‐one of 267 evaluable patients (12%) had a poor response. SCT was performed in 25; using matched unrelated donors in 13, matched sibling donors in 6, cord blood donor in 4, and haploidentical donor in two. The median follow‐up for the 31 poor responding patients was 2.6 years (range 0.4 ‐ 8.1 years) and 3‐year probability of survival 70% (95% CI 59‐77%). Conclusions The poor responders in the NOPHO‐AML 2004 protocol had a favourable prognosis treated with time‐intensive induction followed by SCT.